6y+8x-9y+(-10x)=

Simple and best practice solution for 6y+8x-9y+(-10x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y+8x-9y+(-10x)= equation:


Simplifying
6y + 8x + -9y + (-10x) = 0

Reorder the terms:
8x + (-10x) + 6y + -9y = 0

Combine like terms: 8x + (-10x) = -2x
-2x + 6y + -9y = 0

Combine like terms: 6y + -9y = -3y
-2x + -3y = 0

Solving
-2x + -3y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3y' to each side of the equation.
-2x + -3y + 3y = 0 + 3y

Combine like terms: -3y + 3y = 0
-2x + 0 = 0 + 3y
-2x = 0 + 3y
Remove the zero:
-2x = 3y

Divide each side by '-2'.
x = -1.5y

Simplifying
x = -1.5y

See similar equations:

| 4(-1)(-3)=-1 | | -2.5-5.2=12.8 | | 7a+4b-3a-5b= | | -12+4m=2m+2 | | 6z=4z+12 | | 6z=4z+12 | | 11+4=-5(6x-3) | | -7z+12z^2-12=0 | | 4(x+3)-(6n+6)= | | 39+4y-16=17y-13-4y | | 6(x+4)-9=2x+4(5+x) | | y-5=-5(x+6) | | 20x-16=20x+7 | | 4(x+12)-(6n+6)= | | 2x+7y=k+8 | | 3y^2+65=2y^2+127 | | 20x-16=20x+4 | | 0.85x+0.05(10-x)=0.10(-27) | | -7(3x-3)+6=-21x+27 | | 3x^2+3y^2+15y+9x+12=0 | | 2x(3x-9)-4=2(x-3) | | 6(18.5)-3=x | | 11r^2+28=0 | | -7(3x-3)+6=-21x+7 | | (5+x^4)-(3x^4+4x)=0 | | h(x)=x^2+9x+8 | | 2(-3y-1)+(2y+7)=a | | 2x+5+6x-3+30=180 | | 40.7=5b | | -3(x+9)+6x=-6 | | 3(x^3+2x^2+8x+36)=0 | | -9d-8=154 |

Equations solver categories